EXPLORING THE POTENTIALS OF TECHNOLOGY INTEGRATION FOR TEACHING LANGUAGE SKILLS: A LITERATURE REVIEW - Isry Laila Syathroh; Evie Kareviati; Ayu Lestari; Nurlaila Fitria (IKIP Siliwangi, 2021)
The use of technology has become an essential element in teaching and learning process. Usually, each language class uses some type of technology tools that are used to support and enhance language learning. They are tools to help teachers facilitate their students' language learning. This research focuses on the role of technology in learning English as a foreign and second language. It addresses the significance of technology that allows English language learners to develop their learning abilities. In this paper, the researchers describe the term technology integration, of technology, explain the use of technology in the language classroom, discuss the advantages and challenges of technology integration, and provide some suggestions for better use of these technologies to help learners develop their learning abilities.